(untitled) (Scientific journal of the Fergana State University, 2023)
The category of time and space is global, which makes it possible to reveal the correlation of the national and cultural-specific in the language, literature and culture of the people. The article deals with the issue of historical inversion and folklore chronotope in the works of Abdulla Kadiri. In the depiction of time and space in this novel, every element of reality is in its place. Methods, elements and functions are also analyzed. Inversion, in fact, leads to the fact that mythological and artistic thinking within the framework of the past is limited to the categories of goal, ideal, justice, perfection, the harmonious state of a person, society, etc.